Peningkatan Pemahaman Siswa Farmasi tentang Peran Farmakoekonomi dalam Pelayanan Kesehatan di SMK Bintang Persada Denpasar - Made Dwike Swari Santi; Ni Wayan Rika Kumara Dewi; Gede Terima Yasa (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Pharmacoecomics has been defined as the description and analysis of the costs of drug therapy to health care systems and society. Pharmacoeconomics research identifies, measure, and compares the costs and consequences of pharmaceutical product and service. Within this framework, research and methods related to cost-minimization, cost-effectiveness, quality-of-life and other humanistic assessments are include. In-essence, pharmacoeconomics analysis uses tools for examining the impact of alternative drug therapies and other medical interventions Based on this background, the author is interested to explain about the role of Pharmacoecomics on health service in pharmacist students at Bintang Persada School, Denpasar. Purpose: The purpose of this activity is as a form of implementation of Tri Dharma Stikes Bali Wisnu Dharma Denpasar. Methods: Participants who took part in this activity were 83 students using the pretest and posttest methods. Results: The results obtained were an increase in the pretest score (before being given education) which was 62.11% to 83.22% in the posttest result (after being given education). Conclusion: There is a significant relationship between posttest scores, which increases after education is held, so pharmacoeconomics education needs to be given and pharmaceutical products utilization in health service followed by cost utillity evaluation and cost effectiveness as well as impact evaluation of quality adjusted life years of patients.